Genomic reconstruction and features of glycosylation pathways in the apicomplexan Cryptosporidium parasites - Wang, Dongqiang; Wang, Chenchen; Zhu, Guan (Frontiers in Molecular Biosciences, 2022)
Cryptosporidium is a genus of apicomplexan parasites infecting humans or other vertebrates. The majority of the Cryptosporidium species live in host intestines (e.g., C. parvum, C. hominis and C. ubiquitum), but there are a few gastric species (e.g., C. muris and C. andersoni). Among them, C. parvum is the most important zoonotic species, for which a number of glycoproteins have been reported for being involved in the interacting with host cells. However, little is known on the cryptosporidium glycobiology. Information on the glycosylation pathways in Cryptosporidium parasites remains sketchy and only a few studies have truly determined the glycoforms in the parasites. Here we reanalyzed the Cryptosporidium genomes and reconstructed the glycosylation pathways, including the synthesis of N- and O-linked glycans and GPI-anchors. In N-glycosylation, intestinal Cryptosporidium possesses enzymes to make a simple precursor with two terminal glucoses on the long arm (i.e., Glc5Man5GlcNAc2 vs. Glc3Man9GlcNAc2 in humans), but gastric species only makes a simpler precursor containing only the “core” structure (i.e., Man3GlcNAc2). There is an ortholog of glucosidase II (GANAB) in all Cryptosporidium species, for which the authenticity is questioned because it contains no signal peptide and exist in gastric species lacking terminal glucoses for the enzyme to act on. In O-linked glycosylation, all Cryptosporidium species may attach one-unit HexNAc (GalNAc and GlcNAc) and two-unit Fuc-type (Man-Fuc) glycans to the target proteins. Cryptosporidium lacks enzymes to further process N- and O-glycans in the Golgi. The glycosylphosphatidylinositol (GPI)-anchor in Cryptosporidium is predicted to be unbranched and unprocessed further in the Golgi. Cryptosporidium can synthesize limited nucleotide sugars, but possesses at least 12 transporters to scavenge t nucleotide sugars or transport them across the ER/Golgi membranes. Overall, Cryptosporidium makes much simpler glycans than the hosts, and the N-glycoforms further differ between intestinal and gastric species. The Cryptosporidium N- and O-glycans are neutrally charged and have limited capacity to absorb water molecules in comparison to the host intestinal mucins that are negatively charged and highly expandable in waters.